Antidiabetic DPP-4 Inhibitors Reprogram Tumor Microenvironment That Facilitates Murine Breast Cancer Metastasis Through Interaction With Cancer Cells via a ROS–NF-кB–NLRP3 Axis - Li, Rui; Zeng, Xin; Yang, Meihua; Feng, Jinmei; Xu, Xiaohui; Bao, Liming; Ye, Tingbo; Wang, Xin; Xue, Bingqian; Huang, Yi (Frontiers in Oncology, 2021)
Improvement of understanding of the safety profile and biological significance of antidiabetic agents in breast cancer (BC) progression may shed new light on minimizing the unexpected side-effect of antidiabetic reagents in diabetic patients with BC. Our recent finding showed that Saxagliptin (Sax) and Sitagliptin (Sit), two common antidiabetic Dipeptidyl peptidase-4 inhibitors (DPP-4i) compounds, promoted murine BC 4T1 metastasis via a ROS-NRF2-HO-1 axis in NOD-SCID mice. However, the potential role of DPP-4i in BC progression under immune-competent status remains largely unknown. Herein, we extended our investigation and revealed that Sax and Sit also accelerated murine BC 4T1 metastasis in orthotopic, syngeneic and immune-competent BALB/c mice. Mechanically, we found that DPP-4i not only activated ROS-NRF2-HO-1 axis, but also triggered ROS-dependent NF-кB activation and its downstream metastasis-associated gene levels in vitro and in vivo, while NF-кB inhibition significantly abrogated DPP-4i-driven BC metastasis in vitro. Meanwhile, inhibition of NRF2-HO-1 activation attenuated DPP-4i-driven NF-кB activation while NRF2 activator ALA enhanced NF-кB activation, indicating an essential role of ROS-NRF2-HO-1 axis in DPP-4i-driven NF-кB activation. Furthermore, we also found that DPP-4i increased tumor-infiltrating CD45, MPO, F4/80, CD4 and Foxp3-positive cells as well as myeloid-derived suppressor cells (MDSCs), and decreased CD8-positive lymphocytes in metastatic sites, but did not significantly alter cell viability, apoptosis, differentiation and suppressive activation of 4T1-induced splenic MDSCs. Moreover, we revealed that DPP-4i triggered ROS-NF-kB-dependent NLRP3 inflammasome activation in BC cells, leading to increase of inflammation cytokines such as IL-6, TNF-α, VEGF, ICVM-1, VCAM-1, IL-1β and IL-33, as well as MDSCs inductors GM-CSF, G-CSF, and M-CSF, which play a crucial role in the remodeling of tumor immune-suppressive microenvironment. Thus, our findings suggest that antidiabetic DPP-4i reprograms tumor microenvironment that facilitates murine BC metastasis by interaction with BC cells via a ROS-NRF2-HO-1-NF-kB-NLRP3 axis. This finding not only provides a mechanistic insight into the oncogenic ROS-NRF2-HO-1 in DPP-4i-driven BC progression, but also offers novel insights relevant for the improvement of tumor microenvironment to alleviate DPP-4i-induced BC metastasis.